1972
DOI: 10.1149/1.2404115
|View full text |Cite
|
Sign up to set email alerts
|

Polymethonium-Silver Iodide Compounds as High-Conductivity Solid Electrolytes

Abstract: Polyquaternaryalkylammonium iodide-silver iodide compounds with high ionic conductivity in the solid state have been prepared. The systems (RzN-(CH2),-NRa) I2 --AgI, at 1:12 ratio, give specific conductivities of the order of 10 -2 (ohm • cm)-L For the system octamethyldiethylentriammonium iodide-silver iodide in the ratio 1: 22, the specific conductivity reaches, at room temperature, a value of 5.8 • 10 -2 (ohm • cm) -1 * Electrochemical Society Active Member.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

1972
1972
1995
1995

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…The specific conductance of the solid electrolyte has been found to be 0.029 (ohm • cm) -1, the same value as that reported in a previously mentioned paper (1).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The specific conductance of the solid electrolyte has been found to be 0.029 (ohm • cm) -1, the same value as that reported in a previously mentioned paper (1).…”
Section: Resultssupporting
confidence: 86%
“…Optimizations of porous electrodes must therefore be based upon some model able to predict how these phenomena influence the discharge behavior. During the last decade various mathematical models have been proposed for the theoretical analysis of electrode reactions in porous media (1)(2)(3)(4) the theoretical work in this field has been extensive, comparatively few applications of these models have, however, been made to practical electrodes. In the case of the practically important lead dioxide electrode, used as positive electrode in the lead-acid cell, theoretical and experimental investigations of current distribution have given contradictory results (5-9).…”
Section: Department Of Chemical Technology the Roy Al Institute O~ Tmentioning
confidence: 99%
“…Ionic conduction in the system substituted ammonium iodide-silver iodide was studied extensively by Owens (1), Owens, Christie, and T~edeman (2), and Beradelli et al (3), and many compounds were reported to have the ionic conductivities in the range of 8 • 10 -4 to 6 • 10 -2 (ohm-cm)-I at 25~ From the conductivity measurements of a large number of the systems, Owens e~ al. (2) concluded that the formation of ion conductive compounds was related to the size of organic ammonium ions.…”
mentioning
confidence: 99%
“…In recent years, in order to find high ionic conductivity solids, Ag3SI (1, 2), RbAg415 (3,4), KAg414CN (5), Ag19115P207 (6), double salts composed of silver iodide and some organic compounds (7)(8)(9), and g-A1203 (10) have been examined and several promising results have been achieved. The charge carrier in these compounds is the silver or alkali ion, and no other ion conductors which exhibit high ionic conductivity at ambient temperature have been reported.…”
mentioning
confidence: 99%